Some Aspects to the Rehabilitation of the Vernacular Adobe Architecture - Nemcsics, Ákos; Ürmös, Antal; Gröller, György (International Journal of Engineering and Management Sciences, 2021)
In this paper, we are dealing with the heat-technical modeling, life cycle assessment and the conservation of the vernacular adobe wall house. One of our investigations is directed to the seasonal equalizing property of this wall structure. The reason of this choice of this topic can be found in the fact, that in the old Hungarian folk house construction, the abode wall was popular and a significant fraction of the people living in the countryside are still inhabit these old houses. The Hungarian winter is cold and followed normally by sizzling hot summer. The adobe wall construction is perfect for the local climatic conditions. Due to the on-going global warming up, the ecological importance of these wall constructions is becoming more prominent. Most of these adobe wall constructed houses are already under preservation order, due to their ecological significance and also because they are part of our culture heritage. Their conservation and maintenance problems are briefly described in the paper, too.